The Effect of Arm Muscle Power Abilities on Badminton Backhand Smash: A Systematic Review - Situmorang, Cristeven Tono; Zalukhu, Fans Darno Prianto Osra; Ginting, Risky Cristyan; Gea, Dedi Torman; Manik, Penata (Pusat Pengembangan Olahraga Universitas Pahlawan, 2025)
Research Objectives: This study aimed to systematically review the influence of arm muscle power on badminton backhand smash performance and to identify methodological trends, limitations, and directions for future research. Materials and Methods: Following PRISMA guidelines, electronic searches of PubMed, Scopus, Web of Science, and SPORTDiscus (2010–2025) were conducted. A total of 1,053 records were screened, and 20 studies met the inclusion criteria. Eligible studies included experimental, correlational, and biomechanical investigations focusing on the relationship between upper-limb power and backhand smash performance. Data extraction and quality appraisal were performed independently by two reviewers. Results: The synthesis of 20 studies (N = 1,245) revealed consistent evidence of strong positive associations (r = 0.72–0.95) between upper-limb explosive power and smash velocity, accuracy, or overall effectiveness. Biomechanical analyses highlighted the critical role of the wrist-forearm segment in accelerating racket head speed. Training interventions incorporating resistance, plyometric, and medicine-ball drills led to significant performance gains, with smash velocity improvements ranging from 6–12% over 6–8 weeks. Limitations included heterogeneous power-testing protocols and a lack of longitudinal studies. Conclusions: Arm muscle power plays a decisive role in optimizing badminton backhand smash performance. Coaches should prioritize targeted upper-limb power training, particularly wrist-forearm conditioning, while researchers should pursue standardized, longitudinal studies to deepen causal understanding and refine training strategies.